Multicultural attitudes and beliefs among early education teachers: A comparative study of Poland and Iceland - Teresa Parczewska; Justyna Sala-Suszyńska; Ewa Sosnowska-Bielicz (Multidisciplinary Journal of School Education, 2025)
Research objectives (aims) and problem(s): The article presents the results of a study conducted in Poland and Iceland. Its aim was to compare the attitudes of early childhood education teachers toward multiculturalism. It also sought to examine the relationship between sociocultural factors and the respondents’ multicultural attitudes.